Dual conductive surface engineering of Li-Rich oxides cathode for superior high-energy-density Li-Ion batteries. (May 2019) - Yu, Fu-Da; Que, Lan-Fang; Xu, Cheng-Yan; Wang, Min-Jun; Sun, Gang; Duh, Jenq-Gong; Wang, Zhen-Bo
Abstract: Li-rich (LR) layered oxide cathode for high-energy-density Li-ion batteries are receiving considerable attention. However, their intrinsic issues hinder the implementation of LR in simultaneously achieving higher energy and power densities. Herein, a dual-conductive surface control strategy is proposed. This surface layer contains an electronic conductive carbon nanotube (CNT) skeleton and an ionic conductive heteroepitaxial spinel structure, which endows the LR with the light-weight and self-standing characteristic. As evidenced by prolonged electrochemical and structural evolution, this surface layer can reduce polarization, restrain structural distortion and facilitate fast electronic/ionic diffusion. Density functional theory (DFT) calculations demonstrate a higher electron conductivity with a narrower band gap across the CNT/LR interface than that of pure LR, and reveal a highly connective Li + percolation network and reduced Li + migration energies for the layered-spinel heterogeneous interface. The designed LR cathode presents a high energy density (1077 Wh kg −1 at 0.1 C), excellent rate capability (195 mAh g −1 at 10 C) and superior cycle stability. When utilized as an additive-free cathode for high-voltage full-battery, impressive energy density (645 Wh kg −1 based on the cathode and anode) and ultra-long cycle life (maintaining 87% capacity after 400 cycles) can be achieved. These results and this dual-conductive surface control strategy provide an exciting perspective and avenue for the further development of high-performance electrode material. Graphical abstract: We propose a novel dual-conductive surface control strategy and new insight into the correlation between the surface structure and electrochemical reactivity to ameliorate the LR cathode's inherent issues. The specially designed surface layer endows the LR cathode with the light-weight and self-standing characteristic. The prolonged electrochemical/structural evolution analysis and theoretical study indicate that the designed surface layer can reduce polarization caused by the side reaction, stabilize LR to restrain the structural distortion, and facilitate the fast electronic/ionic diffusion.Image 1 Highlights: Propose a dual-conductive surface control strategy to construct light-weight, self-standing, CNT/spinel coated LR cathode. DFT calculations reveal the electron distribution and narrowed the band gap of the CNT/LR interface model. The layered-spinel hetero-interface equips highly connective Li + percolation networks and reduced Li + migration energies. The designed LR cathode exhibits impressive energy density, excellent rate capability and superior cycle stability.